2021
DOI: 10.1007/s10530-021-02662-w
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal depth distribution and thermal experience of the non-indigenous round goby Neogobius melanostomus in the Baltic Sea: implications to key trophic relations

Abstract: Native to the Ponto-Caspian region, the benthic round goby (Neogobius melanostomus) has invaded several European inland waterbodies as well as the North American Great Lakes and the Baltic Sea. The species is capable of reaching very high densities in the invaded ecosystems, with not only evidence for significant food-web effects on the native biota and habitats, but also negative implications to coastal fishers. Although generally considered a coastal species, it has been shown that round goby migrate to deep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 65 publications
0
22
0
Order By: Relevance
“…During these months, the diet of round goby in Lake Ontario are dominated by dreissenid mussels and growth rates are also predicted to be highest across the annual growing season (Brush et al, 2012; Lee & Johnson, 2005). This contrasts with the autumn–winter period, when round goby migrate offshore to seek the warmest available habitat as represented by the 0–4°C waters the occur at depth during winter stratification (Behrens et al, 2022; Pennuto et al, 2021). Such a seasonal contrast in behavioural thermoregulation can also result in a 5–6‐fold decline in metabolism and bioenergetic performance (Skazkina & Kostyuchenko, 1968).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During these months, the diet of round goby in Lake Ontario are dominated by dreissenid mussels and growth rates are also predicted to be highest across the annual growing season (Brush et al, 2012; Lee & Johnson, 2005). This contrasts with the autumn–winter period, when round goby migrate offshore to seek the warmest available habitat as represented by the 0–4°C waters the occur at depth during winter stratification (Behrens et al, 2022; Pennuto et al, 2021). Such a seasonal contrast in behavioural thermoregulation can also result in a 5–6‐fold decline in metabolism and bioenergetic performance (Skazkina & Kostyuchenko, 1968).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, for δ 13 C and δ 15 N, consumer values may be obfuscated by short‐term changes in habitat and prey resource availability and subsequent exploitation behaviours that are not fully integrated by isotopic turnover kinetics. For example, in the spring–summer months, round goby select nearshore habitats that provide water temperatures approaching the preferred optimum (Behrens et al, 2022; Pennuto et al, 2021). During these months, the diet of round goby in Lake Ontario are dominated by dreissenid mussels and growth rates are also predicted to be highest across the annual growing season (Brush et al, 2012; Lee & Johnson, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing similarity of the respective trophic niches may be due to a higher mobility of round gobies, and migration from the walls to the bottom after the reproductive season. In lake and sea habitats, round gobies migrate to deeper waters (up to >70 m) in winter (Behrens et al, 2021; Carlson et al, 2021). While we do not know if comparable processes happen in rivers of relatively shallow depths (river Rhine in Basel, Switzerland: ca.…”
Section: Discussionmentioning
confidence: 99%
“…The proportion of sneaker males in a population can vary widely, with values between 4% (Cerwenka et al, 2020) and 40% (Bleeker et al, 2017) reported in different ecosystems. Outside of the reproductive season, they show higher mobility, or even migration patterns to deeper waters (Behrens et al, 2021; Carlson et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation